АНАЛІЗ ВПЛИВУ МІГРАЦІЇ НА РОЗВИТОК ЕКОНОМІКИ УКРАЇНИ (International Journal of Innovative Technologies in Economy, 2018)
The main problems that cause labor migration are reviewed. The factors that cause labor migration are examined. Information about the ways of money transfers affect the state of Ukrainian economy is provided. The experience of Ireland regarding the return of migrants is shown. Some organizational steps that can stabilize the situation with labor migration in Ukraine have been worked out. The Umigrant mobile application model for Ukrainians abroad has been developed. The Umigrant mobile application will provide migrants with easy access to reliable information about organizations and services available to them in a particular country: embassies, consulates, migration departments, hospitals and civil society organizations. It will also provide information on migration options and requirements, and will allow migrants to receive alerts on emergencies in a country or region, as well as contacts for emergency assistance.